NGHIÊN CỨU TỈ LỆ VÀ CÁC YẾU TỐ LIÊN QUAN ĐẾN NGUY CƠ TRẦM CẢM Ở THAI PHỤ 3 THÁNG CUỐI THAI KỲ TẠI BỆNH VIỆN ĐA KHOA KHU VỰC LONG KHÁNH (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the prevalence of depression risk and its associated factors among pregnant women in their third trimester at Long Khanh Regional General Hospital in 2025. Materials and Methods: An analytical cross-sectional study with longitudinal follow-up was conducted on 189 pregnant women at 29 weeks of gestation or later. The depression risk was assessed using the Edinburgh Postnatal Depression Scale (EPDS) with a cut-off score of 13. Results: The prevalence of depression risk among pregnant women in the third trimester was recorded at 16.9%. Analysis revealed several factors significantly associated with depression risk, including: unintended pregnancy (OR=13.67), a family history of depression (OR=10.4), adverse family events (OR=8.51), separation/divorce or not living with the husband (OR=8.01), lack of husband's support/not seeking help from the husband when facing difficulties (OR=3.96), marital conflicts (OR=3.87), and poor/near-poor household economic status (OR=3.06). Conclusion: The prevalence of depression risk in the third trimester is 16.9%. Routine depression screening in pregnant women is necessary to provide timely mental health support, with particular attention given to those facing risk factors related to the lack of support from their families and husbands.
Keywords: antenatal depression risk, third trimester, EPDS, associated factors.